ANALISIS PENGELOLAAN MODAL KERJA UNTUK MENILAI RETURN ON INVESTMENT PADA PT GUDANG GARAM, TBK YANG TERDAFTAR DIBURSA EFEK INDONESIA TAHUN 2016-2017 - Fadillah Utami; Mursalin Mursalin; Emma Lilianti (Journal of Management Small and Medium Enterprises (SMEs), 2023)
This study aims to determine working capital management as measured by Working Capital Turnover, Cash Turnover, Accounts Receivable Turnover, and Inventory Turnover to assess Return on Investment (ROI) at PT Gudang Garam, Tbk during the 2016–2020 period. This study uses quantitative methods. The results of Working Capital Turnover indicate that the calculation of Working Capital at PT Gudang Garam, Tbk is in "not good" condition. The results of Cash Turnover show that the calculation of cash flow at PT Gudang Garam, Tbk is in "good" condition. The results of Accounts Receivable Turnover indicate that the calculation of receivables at PT Gudang Garam, Tbk is in "good" condition. The results of Inventory Turnover indicate that the inventory at PT Gudang Garam, Tbk is in "not good" condition. The results of the Return on Investment Turnover show that the calculation of Return on Investment at PT Gudang Garam, Tbk is in "not good" condition. Based on the conclusions from the results of the research, the researchers have suggestions for further improving the effectiveness of the company's overall operations. Keywords: Working Capital Management; Working Capital Turnover; Cash Turnover; Accounts Receivable Turnover; Inventory Turnover Cycle; Return on Investment